STUDENTS’ RESPONSES TOWARD THINK TALK WRITE STRATEGY IN TEACHING WRITING - Ika Yulia Anggraeni; Yanuarti Apsari (IKIP Siliwangi, 2021)
Writing skill is one of the skills that is difficult to learn because we have to know the correct sentence composition and also what we hear must be in accordance with what we write and therefore this skill is very important to learn. The objective of the research is to identify the sudents’ responses toward think talk write (TTW) strategy in teacihng writing skill. The research used descriptive qualitative design. The respondents of this research were eighth grade students of SMP Pasundan 1 Cimahi. The instrument of this research was questionnaire. The result of data analysis shows that students gave positive responses toward TTW strategy. The respondents agree that TTW strategy can increase students’ motivation, TTW Strategy can help students in improving their writing skill and TTW strategy can make teaching and learning process interesting. Keywords: Writing, Think Talk Write (TTW) Strategy, Student’s Responses